Levels of Interleukin-18 Are Markedly Increased in Helicobacter pylori–Infected Gastric Mucosa among Patients with Specific IL18 Genotypes - Sakai, Kyoko (2008)
BACKGROUND: The cellular immune response in gastric mucosa infected with Helicobacter pylori is proposed to be predominantly of the T helper cell type 1 type. METHODS: Interleukin (IL)–18, IL-12, and interferon (IFN)–γ levels were measured in gastric mucosal biopsy specimens by reverse-transcription polymerase chain reaction (PCR) and by enzyme-linked immunosorbent assay; IL18 polymorphisms were determined by PCR. RESULTS: Biopsy specimens from 128 patients (56 with nonulcer dyspepsia, 28 with gastric ulcers, 28 with duodenal ulcers, and 16 with gastric cancer) were examined; 96 patients had H. pylori infection. IL-18 levels were markedly up-regulated in mucosa infected with H. pylori (P < .001), whereas IL-12 and IFN-γ levels were independent of H. pylori status. IL-18 levels correlated with IFN-γ levels only in infected patients (R = 0.31 to R = 0.51). IL-18 levels were the determining factor for monocyte infiltration in H. pylori–infected mucosa (P < .001). H. pylori–infected patients displaying IL18 –607C/C and –137G/G had higher IL-18 levels than did those with other genotypes and were more likely to experience treatment failure. CONCLUSION: H. pylori infection induces IL-18 in the gastric mucosa. H. pylori–infected patients with IL18 –607C/C and –137G/G have higher IL-18 levels, which causes severe gastric inflammation. IL18 genotype might be a marker for predicting the effects of eradication therapy.